Teachers’ perceptions of using virtual reality technology in classrooms: A large-scale survey - Khukalenko, Iuliia Sergeevna; Kaplan-Rakowski, Regina; An, Yunjo; Iushina, Vera Dmitrievna (Education and information technologies, 2022)
High-immersion virtual reality (VR) technology is often associated with gaming. Yet, it is increasingly popular in educational contexts due to its potential to engage and motivate learners. Prior to VR technology integration in the classroom, the acceptance or resistance toward VR needs to be explored. This paper reports the results obtained from a large-scale ( N = 20,876) survey on teachers’ attitudes toward the use of VR for education. The survey explored the relationships between the teachers’ VR integration level and their instructional approaches, as well as the frequency of VR use. Furthermore, the survey yielded answers on the relationship between the availability of information technology (IT) personnel and the frequency of VR use. Overall, teachers had moderately positive perceptions of the use of VR in education. There was no strong correlation between instructional approaches and the level of VR integration, but lower levels of VR integration were associated with more traditional teaching approaches. The results revealed a positive correlation between the level of VR integration and the frequency of VR use. However, the VR frequency use had a weak correlation with the availability of IT personnel.